Molecular Biology of Valvular Heart Disease - Rajamannan, Nalini M.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
This book presents the cellular details and the basic molecular biology approaches for understanding cardiac valvular disease. It provides novel cellular targets for developing future clinical trials and comprehensive clinical discussion of this expanding field. Molecular Biology of Valvular Heart Disease will guide physicians on the potential medical therapies to treat valvular heart disease while providing a platform for cellular targeting of valvular heart disease. Residents and fellows in cardiology, interventional cardiology, cardiac surgery, and current and future valve biologists alike will find this book to be an invaluable resource for developing further interest and understanding of the cellular basis for cardiac valvular disease treatment.
Calcific Aortic Valve Disease: The Role of the Stem Cell Niche -- In vitro Cell Culture Model of Calcification: Molecular Regulation of Myofibroblast Differentiation to an Osteoblast Phenotype -- Aortic Valve Apoptosis, Cell Proliferation and Atherosclerosis in Experimental Hypercholesterolemia -- Experimental Model of Aortic Valve Calcification to Induce Osteoblast Differentiation -- Development of an Experimental Model of Mitral Valve Regurgitation via Hypertrophic Chondrocytes -- Testing Drug Eluting Paclitaxel Balloon Valvuloplasty in an Experimental Model of Aortic Stenosis -- Ex vivo model for Bioprosthetic Valve Calcification via Stem Cell Differentiation -- Experimental Hypercholesterolemia in Genetic ApoE-/-/Lrp5-/- Mice: Proof of Principle -- Wnt3a-Lrp5 mediated Bicuspid Aortic Valve Disease -- Mouse Models of Calcific Aortic Valve Disease -- Hemodynamic Mechanisms of Bicuspid Aortic Valve Calcification and Aortopathy -- Bioreactor and biomaterial platforms for investigation of mitral valve biomechanics and mechanobiology -- Identification of early pathological events in calcific aortic valve disease by molecular imaging -- Role of ectonucleotidases and purinergic receptors in calcific aortic valve disease -- In vitro model of Drug Testing -- Application of the LDL-Density-Pressure Theory: The Mitral Valve -- Application of The LDL-Density-Radius Theory: The Aortic Valve.
Keywords: Cardiology; Cardiology